The new locally endemic genus Yazdana (Caryophyllaceae) and patterns of endemism highlight the high conservation priority of the poorly studied Shirkuh Mountains (central Iran). Issue 3 (24th March 2020) - Noroozi, Jalil; Pirani, Atefeh; Moazzeni, Hamid; Mahmoodi, Mohammad; Zare, Golshan; Noormohammadi, Alireza; Barfuss, Michael H.J.; Suen, Michael; Schneeweiss, Gerald M.
Abstract: Although mountain ranges are often recognized as global biodiversity hotspots with a high level of endemism, diversity and biogeographic connections of isolated and weakly explored mountains remain poorly understood. This is also the case for Shirkuh Mts. in central Iran. Here, Yazdana shirkuhensis gen. & spec. nov. (Caryophylleae, Caryophyllaceae) is described and illustrated from the high alpine zone of this mountain. Molecular phylogenetic analyses of nuclear and plastid DNA sequence data show that Y. shirkuhensis is related to Cyathophylla and Heterochroa (tribe Caryophylleae). The newly described genus and species accentuate Shirkuh Mts. as a center of endemism, which harbors a high number of narrowly distributed species, mostly in high elevations reaching alpine habitats. As this area is currently not protected, a conservation priority is highlighted for high elevations of Shirkuh Mts.